Pengendalian Persediaan Bahan Baku Keripik Balado Salsabila Menggunakan Metode Silver Meal Heuristic - Adinda, Viola; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2023)
Inventory is a factor that decides the smoothness of production and sales so inventory must be controlled to produce minimum costs. The problems that occur in the Keripik Balado Salsabila Business are the use of erratically raw material supplies and the absence of raw material control, so a method is needed to deal with these issues. The research purpose is to compare the total inventory of raw materials between company policies and the method of Silver Meal Heuristic. The benefits of this method are to control inventory and reduce inventory costs. In controlling inventory, the data that is calculated is the five main raw materials for Keripik Balado, including cassava, oil, chili, salt, sugar and lime. The results obtained using the Silver Meal Heuristic method indicated savings in raw material inventory costs of IDR3.829.000 with a total efficiency of 16%. Thus, the method of Silver Meal Heuristic is better to use because it produces a smaller total inventory cost compared to company policy.